2015
DOI: 10.1186/s13000-015-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of circulating microRNA-328 is associated with poor prognosis in patients with acute myeloid leukemia

Abstract: BackgroundDysregulation of circulating miR-328 has been identified in several tumors and is associated with prognosis of patients. However, the expression pattern of miR-328 and the impact on prognosis has not yet been studied in acute myeloid leukemia (AML). The purpose of this study is to investigate the expression status of miR-328 and its clinical significance in AML patients.MethodsRNA was extracted from plasma of 176 patients with newly diagnosed AML and 70 healthy volunteers. The miR-328 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Diaz-Beya et al reported that high miR-3151 expression was commonly found in AML patients and obtained shorter disease-free, OS, lower CR rate and higher cumulative incidence of relapse compared with low expressers [67]. The underexpression of miR-328 in AML patients had poor clinical outcome and may provide a diagnostic and prognostic biomarker [68]. MiR-34a expression was negatively correlated with aggressive clinical variable.…”
Section: Micrornas As Biomarkers For Prognosis In Acute Myeloid Leukemiamentioning
confidence: 99%
“…Diaz-Beya et al reported that high miR-3151 expression was commonly found in AML patients and obtained shorter disease-free, OS, lower CR rate and higher cumulative incidence of relapse compared with low expressers [67]. The underexpression of miR-328 in AML patients had poor clinical outcome and may provide a diagnostic and prognostic biomarker [68]. MiR-34a expression was negatively correlated with aggressive clinical variable.…”
Section: Micrornas As Biomarkers For Prognosis In Acute Myeloid Leukemiamentioning
confidence: 99%
“…In nasopharyngeal carcinoma, miR-328 is considered as a potential prognostic and therapeutic marker due to its inhibiting effect on the epithelial-mesenchymal transition of nasopharyngeal carcinoma cells (26). Liu et al (27) demonstrated that low miR-328 expression can predict a poor prognosis in patients with acute myeloid leukemia. Previous studies also reported that low miR-328 expression level is associated with poor survival in patients with high-grade glioma, and that miR-328 can impair glioma cell proliferation and invasive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Tako je profil izražaja miRNK u RAEB-1 (refraktorna anemija s viškom blasta tipa I) bio sličan izražajima kod IPSS-a niskog rizika, dok je profil izražaja miRNK pri MDS-u RAEB-2 (refraktorna anemija s viškom blasta tipa II) pokazao sličnost s onime u bolesnika s AML-om. [34][35][36] Jedna od studija koje su pokušale povezati izražaj različitih miRNK s poznatim prognostičkim parametrima uključila je 44 bolesnika s MDS-om i definirala 68 miRNK koji su bili različitog izražaja među bolesnicima s MDS-om visokog rizika i s onime niskog rizika. Izdvojen je miRNK-181b koji je bio pojačano izražen u obje grupe, ali je njegov pojačani izražaj u grupi s MDS-om niskog rizika bio povezan s kraćim preživljenjem.…”
Section: Izražaj Mirnk U Mds-uunclassified